INNOVATIVE DEVELOPMENTS IN AMLODIPINE DRUG DELIVERY SYSTEMS: A COMPREHENSIVE LITERATURE REVIEW - Desnita, Rise (Journal Pharmacy Of Tanjungpura, 2025)
Amlodipine is a dihydropyridine calcium channel antagonist massively prescribed in the management of hypertension and angina with favorable pharmacokinetics characterized by a long elimination half-life. Challenges associated with conventional formulations include dose-dependent side effects, specific patient populations, and therapeutic potential that has not been harnessed. Recent studies have led to a paradigm shift from merely enhancing basic bioavailability to optimizing pharmacokinetics, reducing side effects, and enabling the direct delivery of treatment to where it is needed. Some attempts have been made to use orodispersible tablets (ODTs) for improved patient compliance, as well as inclusion complexes and solid dispersions, among others, in nanotechnology systems, including nanostructured lipid carriers (NLCs), nanoemulsions, and nanodiamonds. Nanoemulsions showed an increase in oral bioavailability (475%) with heart targeting, while nanodiamonds discovered a pathway to the brain delivery of amlodipine for neuroprotective applications. Floating microspheres prepared have proved controlled release over 20 hours. Conventional formulations are still very attractive; however, the new drug delivery systems can optimize therapy, improve comfort and compliance of patients, and enhance the clinical scope amidst vast potential. Such development of nanoemulsions for better bioavailability, besides further clinical validation regarding trials on humans about safety and efficacy, constitutes one of the main recommendations.